Internalizing spiritual values to cultivate student character: a phenomenological study in islamic elementary education - Unung Lisnawati; Wardatul Hayati; Nia Kurnia; Jaka Nugraha; Uus Ruswandi (University of Muhammadiyah Malang, 2026)
Islamic Religious Education (IRE) in Madrasah Ibtidaiyah faces significant challenges in the digital era, where an overemphasis on cognitive aspects of learning may undermine the development of students' religious character. This study aims to analyze strategies for integrating spiritual values and their relevance in strengthening the religious character of students at MI Sunan Gunung Djati, Bandung. Employing a descriptive qualitative approach with a field study design, data were collected through participatory observations and in-depth interviews with subject teachers. The data were subsequently analyzed using thematic analysis, involving transcription, coding, theme grouping, and drawing conclusions. The findings reveal that the integration of spiritual values is systematically implemented through the tarbiyah bil 'adah approach, which is manifested in daily worship practices, literacy programs, Quran memorization activities, and teacher role modeling during the learning process. This integration is further reinforced by the application of a dual curriculum and a humanistic approach that fosters the internalization of spiritual values, aligning with students' cognitive and psychosocial development stages. In conclusion, the contextual and sustainable integration of spiritual values is instrumental in reinforcing students' religious character and serves as an effective strategy in addressing the educational challenges of the digital age.